The Effect of Imagery Exercise and Progressive Muscle Relaxation on Anxiety and Concentration in Soccer Athletes - Zakir Burhan; Lalu Yoga Vandita (IKIP Mataram, 2021)
This study aims to examine the effect of applying imagery and progressive muscle relaxation exercises on the level of anxiety and concentration in Persatu Darek FC athletes. This study uses a quantitative approach with a quasi experimental design (matching-only design). The research sample consisted of 33 athletes who were divided into 3 groups of athletes (11 athletes in each group), each of which was given a pretest and posttest. The experimental group I was given an imagery exercise program, the experimental group II was given a progressive muscle relaxation exercise program, and the third group was a control (conventional exercise). The test instrument to measure the level of concentration is the grid concentration exercise test, while the anxiety test uses a sport anxiety scale. Data analysis in this study used a different test (t-test) and multivariate analysis of variance. The results of the study showed that there was a significant effect of giving progressive muscle relaxation and imagery exercises to the level of anxiety in soccer players. However, it has no effect on conventional exercise modes. The provision of progressive muscle relaxation and imagery exercises also affects concentration in soccer players, and this does not apply to conventional training modes. In this study, we also found that there was no difference in the effect of the concentration variables and the level of anxiety together. Therefore, it can be concluded that neither of the two methods of mental exercise (imagery and progressive muscle relaxation) has a more effective effect on concentration and anxiety levels. The recommendation from the results of this study is that mental exercise conduction (imagery and progressive muscle relaxation) is very important for soccer players as a non-physical exercise mode that is very useful for reducing anxiety and increasing concentration.